Halogen-free laminated board base paper as well as preparation method and application thereof
By optimizing the material ratio and preparation process, plant fibers, composite wet strength agents and composite flame retardants are used to form a chemical crosslinking network, which solves the flame retardancy, flexibility and mechanics of existing halogen-free laminated board substrates. Inadequate performance and heat resistance have achieved high performance and high reliability laminated substrates.
Patent Information
- Application Number
- CN202411812170.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing halogen-free laminated board substrates have shortcomings in flame retardancy, flexibility, mechanical properties and heat resistance, which are difficult to meet the needs of modern electronics industry for high-performance and high-reliability materials.
By optimizing the material ratio and preparation process, plant fibers, composite wet strength agents and composite flame retardants are used to form a rich and stable chemical crosslinking network, which improves the flame retardancy, flexibility, mechanical properties and resistance of laminated substrates. Thermal properties.
It realizes the high flame retardancy, good flexibility, excellent mechanical properties and high heat resistance of laminated substrate paper, meeting the demand of modern electronic industry for high-performance and high-reliability materials.
Smart Images

Figure BDA0005180803150000021 
Figure BDA0005180803150000061 
Figure BDA0005180803150000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper clad laminate substrate base paper, and specifically relates to a halogen-free laminate base paper and a preparation method and application thereof. Background Art
[0002] In the current electronics industry, laminate base paper is the core material of printed circuit boards (PCBs), and its performance is directly related to the reliability, safety and service life of electronic products. With the continuous miniaturization and integration of electronic products and the continuous expansion of application fields, the performance requirements for laminate base paper are also increasing. Halogen-free laminate base paper has deficiencies in flame retardancy, flexibility, mechanical properties and heat resistance, and it is difficult to meet the high standards of the modern electronics industry.
[0003] Traditional laminate base paper often uses halogen compounds as flame retardants to improve its flame retardant properties. However, halogen compounds will produce toxic and harmful gases during combustion, causing serious harm to the environment and human health. With the increase of global environmental awareness, the demand for halogen-free, non-toxic and environmentally friendly laminate base paper is becoming increasingly urgent. Therefore, the development of halogen-free laminate base paper with high flame retardancy has become one of the current research hotspots.
[0004] In the manufacturing process of electronic products, laminate base paper needs to go through multiple bending, folding and cutting processes. Therefore, good flexibility is one of the essential properties of laminate base paper. However, traditional laminate base paper often has deficiencies in flexibility, and is prone to problems such as breakage and delamination, which affects the overall performance and reliability of the product.
[0005] The mechanical properties of laminate base paper, including tensile strength, tear strength, impact strength, etc., are directly related to its service life and reliability in electronic products. Traditional laminate base paper often has deficiencies in mechanical properties and cannot meet the needs of modern electronic products for high-strength and high-toughness materials.
[0006] During the operation of electronic products, laminate base paper needs to withstand thermal stress in high temperature environments. Therefore, good heat resistance is one of the essential properties of laminate base paper. However, traditional laminate base paper is prone to deformation and softening in high temperature environments, affecting the overall performance and reliability of the product.
[0007] In view of the problems existing in the existing halogen-free laminate base paper in terms of wet strength, toughness, impact strength, flame retardancy and flexibility, it is urgent to develop a new type of halogen-free laminate base paper to meet the market demand for high-performance and high-reliability electronic products. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a halogen-free laminate base paper with high flame retardancy, good flexibility, good mechanical properties and high heat resistance, and a preparation method and application thereof. The present invention aims to improve the flame retardancy, flexibility, mechanical properties and heat resistance of the laminate base paper by optimizing the material ratio and preparation process to meet the needs of the modern electronic industry for high-performance and high-reliability materials.
[0009] In order to achieve the above object, the present invention discloses the following technical solutions:
[0010] In a first aspect, the present invention provides a halogen-free laminate base paper, wherein the raw materials for preparing the halogen-free laminate base paper include plant fiber, a composite wet strength agent and a composite flame retardant;
[0011] The plant fibers include softwood fibers, hardwood fibers, cotton fibers, and peanut shell fibers;
[0012] The composite wet strength agent includes JH-1225 wet strength agent and polyethyleneimine resin;
[0013] The composite flame retardant comprises cardanol-modified phenolic resin and ammonium polyphosphate flame retardant;
[0014] The method for preparing the halogen-free laminate base paper comprises the following steps:
[0015] S1-1. The plant fiber is mixed with a composite wet strength agent and slurried, and then formed on the net to obtain base paper;
[0016] S1-2. The base paper is immersed in a composite flame retardant and then dried to obtain the halogen-free laminate base paper.
[0017] Preferably, the plant fiber comprises the following components by weight:
[0018]
[0019] Further preferably, the fiber length of the hardwood fiber is 0.6-1.0 mm, the fiber length of the softwood fiber is 3.1-3.5 mm, the fiber length of the cotton fiber is 10-15 mm, and the fiber length of the peanut shell fiber is 0.15-0.27 mm.
[0020] Preferably, the composite wet strength agent comprises the following components in parts by mass:
[0021] JH-1225 wet strength agent 20 parts;
[0022] 5-7 parts of polyethyleneimine resin.
[0023] Preferably, the composite flame retardant comprises the following components in parts by mass:
[0024] 20-30 parts of cardanol modified phenolic resin;
[0025] 10 parts of ammonium polyphosphate flame retardant.
[0026] Further preferably, the preparation method of the cardanol-modified phenolic resin comprises the following steps:
[0027] S1. Cashew nut shell liquid, phenol and formaldehyde aqueous solution were put into a reactor in a mass ratio of 1:4:6 and stirred at a stirring speed of 500 r / min for 1 h, wherein the concentration of the formaldehyde aqueous solution was 30 wt%;
[0028] S2. Adding aqueous hydrochloric acid to adjust the system pH = 2, heating the reactor to 60 ° C and reacting for 10 hours to obtain a polymer product, and the obtained polymer product is self-flowing to a dehydration kettle, wherein the concentration of the aqueous hydrochloric acid solution is ≥95wt%;
[0029] S3. Heat the dehydration kettle to 130°C, perform high-temperature dehydration on the polymerization product for 1 hour, reduce the temperature to 90°C, turn on the vacuum pump for vacuum dehydration, and obtain cardanol-modified phenolic resin, wherein the vacuum dehydration time is 6 hours and the vacuum degree is 0.09Mpa.
[0030] More preferably, the cashew nut shell liquid contains ≥80 wt % of cardanol.
[0031] Preferably, when the plant fiber is mixed with the composite wet strength agent, the added amount of the composite wet strength agent is (10-13) g of the composite wet strength agent per 100 g of absolute dry weight of the plant fiber.
[0032] In a second aspect, the present invention provides a method for preparing the halogen-free laminate base paper according to the first aspect, the preparation method comprising the following steps:
[0033] S2-1. Place coniferous wood fiber, hardwood wood fiber, cotton fiber and peanut shell fiber in a hydraulic pulper according to a ratio for mixing and crushing, and obtain crushed pulp after crushing in the hydraulic pulper for 12-20 minutes. The crushed pulp is transported to a pulp storage tank, and then beaten by a deflaker and two disc refiners in series, so that the beating degree of the crushed pulp is controlled at (20-23) ° SR, and the fiber wet weight is (1.0-1.5) g, to obtain qualified pulp;
[0034] S2-2. The qualified slurry is transported to a slurry mixing tank, and the composite wet strength agent is added thereto, and then the slurry is mixed, wherein (10-13) g of the composite wet strength agent is added to every 100 g of the absolute dry amount of the qualified slurry to obtain a modulated slurry;
[0035] S2-3. Then, the pulp after the adjustment is sent to the pressure screen for screening after passing through the first-stage three-stage purification system of good pulp countercurrent, dilution in the white water tower and pulp flushing by the pulp flushing pump to obtain the pulp on the screen; the pulp on the screen is wet-formed in the screen part of the front box of the screen through the stabilizing box and the head box to obtain the wet paper web; the wet paper web is pressed and dried to obtain the base paper, and the moisture content of the base paper is ≤10%;
[0036] S2-4. The composite flame retardant and the solvent are mixed at a material-liquid ratio of 1:5 g / mL to prepare an impregnation solution, the base paper is immersed in the impregnation solution for 50 seconds, and then extruded, pressed and dried to obtain a halogen-free laminate base paper, the halogen-free laminate base paper having a thickness of 0.270 ± 0.02 mm and a basis weight of 140 g / m 2 ;
[0037] The solvent is a mixture of 65 wt % ethanol aqueous solution and 60 wt % acetone aqueous solution in a volume ratio of 1:1.
[0038] In a third aspect, the present invention provides the use of the halogen-free laminate base paper described in the first aspect or the second aspect in copper clad laminates or prepregs.
[0039] In the present invention:
[0040] The outer surface of peanut shell fiber is relatively rough and contains a waxy layer, which promotes the overall water resistance and chemical resistance of the base paper. At the same time, peanut shell fiber has a porous network structure. The high lignin and low hemicellulose content make the peanut shell fiber aggregate in a tile-like structure. This structure enables it to improve the toughness and strength of the base paper and reduce its warping after being compounded with hardwood fiber, coniferous wood fiber and cotton fiber in a specific ratio.
[0041] As a polymer containing primary amines, secondary amines and tertiary amines and having a branched structure, polyethyleneimine resin has a high cationic density. It forms hydrogen bonds with the hydroxyl groups on the fiber through cationic tertiary amines, primary amines and other functional groups, thereby enhancing the wet strength of the paper. At the same time, JH-1225 wet strength agent is also a cationic polymer. Polyethyleneimine resin and JH-1225 wet strength agent can significantly improve the wet strength and dry strength of copper clad laminate substrate paper after compounding at a specific ratio, and also improve the toughness and strength performance of the substrate paper.
[0042] Compared with unmodified phenolic resin, cardanol-modified phenolic resin has a higher carbon residue rate and better thermal stability, and can improve the thermal stability of copper-clad laminate substrates; ammonium polyphosphate, as a non-halogen flame retardant with excellent performance, can generate phosphates, amino cyclized products and carbon compounds during combustion when used in combination with cardanol-modified phenolic resin. These products can form a continuous and dense protective layer, effectively preventing the exchange of heat and combustibles during combustion, thereby achieving the purpose of flame retardancy; the present invention has found that the combination of cardanol-modified phenolic resin and ammonium polyphosphate produces a certain synergistic effect, which can further improve the flame retardant properties and thermal stability of copper-clad laminate substrates.
[0043] Beneficial effects of the present invention:
[0044] The laminated board base paper provided by the present invention is prepared from plant fibers of a specific composition, a composite wet strength agent of a specific composition and a composite flame retardant of a specific composition. The plant fibers, the composite wet strength agent and the composite flame retardant form a rich and stable chemical cross-linking network, so that the laminated board base paper has excellent adhesive impregnation, flame retardancy, heat resistance, mechanical strength, flexibility and processability. DETAILED DESCRIPTION
[0045] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0046] Unless otherwise specified, the test methods used in the specific implementation methods are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels; the percentages mentioned in the specific implementation methods, unless otherwise specified, are all mass percentages.
[0047] In the present invention:
[0048] Plant fibers: including hardwood fibers, softwood fibers, cotton fibers and peanut shell fibers, wherein the hardwood fibers have a fiber length of 0.6-1.0 mm, the softwood fibers have a fiber length of 3.1-3.5 mm, the cotton fibers have a fiber length of 10-15 mm, and the peanut shell fibers have a fiber length of 0.15-0.27 mm, purchased from Henan Huining Paper Co., Ltd.;
[0049] JH-1225 wet strength agent: Model JH-1225, a water-soluble thermosetting resin, purchased from Qingzhou Jinhao New Materials Co., Ltd.;
[0050] Polyethyleneimine resin: model SP-003, purchased from Nippon Shokubai;
[0051] Cashew nut shell liquid: containing ≥80wt% cardanol, purchased from Shanghai Dayi Biomaterial Co., Ltd.;
[0052] Flame retardant: ammonium polyphosphate flame retardant, purchased from Hefei Wanran New Material Technology Co., Ltd.;
[0053] Other raw materials are commercially available.
[0054] Preparation of cardanol modified phenolic resin:
[0055] S1. Cashew nut shell liquid, phenol and formaldehyde aqueous solution were put into a reactor in a mass ratio of 1:4:6 and stirred at a stirring speed of 500 r / min for 1 h, wherein the concentration of the formaldehyde aqueous solution was 30 wt%;
[0056] S2. Adding aqueous hydrochloric acid to adjust the system pH = 2, heating the reactor to 60 ° C and reacting for 10 hours to obtain a polymer product, and the obtained polymer product is self-flowing to a dehydration kettle, wherein the concentration of the aqueous hydrochloric acid solution is ≥95wt%;
[0057] S3. Heat the dehydration kettle to 130°C, perform high-temperature dehydration on the polymerization product for 1 hour, reduce the temperature to 90°C, turn on the vacuum pump for vacuum dehydration, and obtain cardanol-modified phenolic resin, wherein the vacuum dehydration time is 6 hours and the vacuum degree is 0.09Mpa.
[0058] Preparation of composite wet strength agent:
[0059] The JH-1225 wet strength agent and the polyethyleneimine resin are mixed uniformly in a mass ratio of 20:(5-7) to obtain a composite wet strength agent.
[0060] Preparation of composite flame retardant:
[0061] A 65 wt % ethanol aqueous solution and a 60 wt % acetone aqueous solution were mixed in a volume ratio of 1:1 to obtain a solvent, and a cardanol-modified phenolic resin and an ammonium polyphosphate flame retardant were put into a reactor in a mass ratio of (2-3):1, and the solvent was added to a material-liquid ratio of 1:5 g / mL. The mixture was mixed and stirred at a speed of 1000 r / min to uniformly dissolve to obtain a composite flame retardant.
[0062] Preparation of halogen-free laminate base paper:
[0063] 1. Preparation steps of the embodiment
[0064] Step (1), placing coniferous wood fiber, hardwood wood fiber, cotton fiber and peanut shell fiber in a mass ratio of 1: (1.5-2): (0.5-0.7): (0.2-0.5) in a hydraulic pulper for mixed crushing, crushing in the hydraulic pulper for 12-20 minutes to obtain crushed pulp, conveying the crushed pulp to a pulp storage tank, and then beating the crushed pulp in a manner of a deflaker and two disc refiners connected in series, so that the beating degree of the crushed pulp is controlled at (20-23) ° SR, and the fiber wet weight is (1.0-1.5) g, so as to obtain qualified pulp;
[0065] Step (2), conveying the qualified pulp to a pulping tank, adding the prepared composite wet strength agent thereto and then performing pulping, wherein (10-13) g of the composite wet strength agent is added to every 100 g of the qualified pulp (absolute dry weight: the mass of the fiber after removing water) to obtain a prepared pulp;
[0066] Step (3), the slurry after the adjustment is then sent to the pressure screen for screening after passing through the first-stage three-stage purification system of good pulp countercurrent, dilution in the white water tower and slurry flushing by the slurry flushing pump to obtain the slurry on the screen; the slurry on the screen is wet-formed in the screen part of the front box through the stabilizing box and the head box to obtain the wet paper web; the wet paper web is pressed and dried to obtain the base paper, and the moisture content of the base paper is ≤10%;
[0067] Step (4), using the composite flame retardant prepared above as an impregnation liquid, impregnating the base paper in the impregnation liquid for 50 seconds, and then extruding, pressing and drying to obtain a halogen-free laminate base paper, the halogen-free laminate base paper having a thickness of 0.270±0.02mm and a basis weight of 140g / m 2 .
[0068] 2. Specific Parameters of the Implementation Example
[0069] The specific parameters are shown in Table 1 below.
[0070] Table 1 Preparation parameters of Examples 1-4
[0071]
[0072]
[0073] 3. Preparation of Comparative Examples
[0074] In order to prove the necessity of the raw materials provided by the present invention, a comparison experiment of omitting or replacing the raw materials was conducted. On the basis of Example 3, the raw materials were omitted or replaced. The specific operation was as follows:
[0075] Comparative Example 1: The mass ratio of the plant fiber coniferous wood fiber, broadleaf wood fiber and cotton fiber in step (1) is adjusted to 1:4:0.7 (a conventional ratio on the market), and the peanut shell fiber is missing. The rest is consistent with Example 3;
[0076] Comparative Example 2: The mass ratio of the plant fiber coniferous wood fiber, broadleaf wood fiber and cotton fiber in step (1) is adjusted to 1:1.8:0.6, and the peanut shell fiber is missing. The rest is consistent with Example 3;
[0077] Comparative Example 3: The polyethyleneimine resin in the composite wet strength agent in step (2) is replaced with a polyurethane resin, the polyurethane resin model PU-D201, purchased from Hefei Huayue New Materials Technology Co., Ltd., the mass ratio of JH-1225 wet strength agent to polyurethane resin in the composite wet strength agent is 20:6, and the rest is consistent with Example 3;
[0078] Comparative Example 4: The composite wet strength agent in step (2) is replaced with JH-1225 wet strength agent alone, and the rest is the same as in Example 3;
[0079] Comparative Example 5: The composite wet strength agent in step (2) is replaced by polyethyleneimine resin alone, and the rest is the same as in Example 3;
[0080] Comparative Example 6: The mass ratio of JH-1225 wet strength agent to polyethyleneimine resin in the composite wet strength agent in step (2) was adjusted to 20:3, and the rest was consistent with Example 3;
[0081] Comparative Example 7: The mass ratio of JH-1225 wet strength agent to polyethyleneimine resin in the composite wet strength agent in step (2) was adjusted to 20:9, and the rest was consistent with Example 3;
[0082] Comparative Example 8: The cardanol-modified phenolic resin of the composite flame retardant in step (4) is replaced with phenolic resin, the phenolic resin is purchased from Shandong Yonghui New Materials Co., Ltd., the mass ratio of phenolic resin to ammonium polyphosphate flame retardant is 2.5:1, and the rest is consistent with Example 3;
[0083] Comparative Example 9: The mass ratio of the cardanol-modified phenolic resin and the ammonium polyphosphate flame retardant in the composite flame retardant in step (4) is adjusted to 1:1, and the rest is consistent with Example 3;
[0084] Comparative Example 10: The mass ratio of the cardanol-modified phenolic resin and the ammonium polyphosphate flame retardant in the composite flame retardant in step (4) is adjusted to 4:1, and the rest is consistent with Example 3;
[0085] Comparative Example 11: The ammonium polyphosphate flame retardant in the composite flame retardant in step (4) is replaced by hexaphenoxy cyclotriphosphazene flame retardant, the hexaphenoxy cyclotriphosphazene flame retardant is purchased from Qingdao Zhenguang Functional Materials Technology Co., Ltd., the mass ratio of cardanol modified phenolic resin and hexaphenoxy cyclotriphosphazene flame retardant is 2.5:1, and the rest is consistent with Example 3.
[0086] Laminated board base paper performance test
[0087] The laminate base paper prepared above was used as the core material to prepare a paper-based copper-clad laminate for performance testing. The specific method is as follows:
[0088] (1) The laminate base paper is impregnated with an adhesive to obtain a prepreg, and the prepreg is heated in an oven at 130° C. for 4 minutes to obtain a prepreg, and the prepreg is pressed at 0.7±0.2 MPa for 6 minutes, and then cut into a required size to obtain a paper-based prepreg;
[0089] (2) The five paper-based prepregs and one coated copper foil were stacked and pressed by a hot press under controlled temperature and pressure for 90 minutes. The pressing conditions were as follows: the pressure was gradually increased from 0 MPa to 4 MPa in the first 5 minutes, and then gradually increased from 4 MPa to 8.5 MPa. The hot pressing temperature was 127°C to obtain a 1.6 mm thick paper-based copper-clad laminate.
[0090] 1. First, perform the following performance tests on the laminate base paper:
[0091] 1.1 Limiting oxygen index LOI test: According to the standard GB / T 2406, the flammability of the laminate base paper is tested. The larger the index, the less likely it is to burn.
[0092] 1.2 Wet strength: in accordance with standard GB / T 1040.2;
[0093] 1.3 Tensile strength: in accordance with standard GB / T 1040.2.
[0094] 2Then the paper-based copper clad laminate is subjected to the following performance tests:
[0095] 2.1 Flame retardancy: tested in accordance with UL-94 standard;
[0096] 2.2 Thermal stress: in accordance with IPC-TM-6502.4.13.1 method;
[0097] 2.3 Maximum bending deflection: Tested in accordance with IPC-TM-6502.4.4 method;
[0098] 2.4 Maximum bending load: Tested in accordance with IPC-TM-6502.4.4 method;
[0099] 2.5 Water absorption: measured according to IPC-TM-6502.6.2.1 method;
[0100] 2.6 Impact strength: tested in accordance with GB / T 1843-2008.
[0101] The test results are shown in Table 2 below:
[0102] Table 2 Performance test results
[0103]
[0104] Result analysis:
[0105] According to the performance test data in Table 2, the laminate base paper provided by the present invention can be used as the core material of the copper clad laminate to effectively enhance the performance of the copper clad laminate. The selection and proportion of the fiber pulp in the laminate base paper, the compounding of the composite wet strength agent and the compounding of the composite flame retardant can significantly improve the heat resistance and flame retardancy of the copper clad laminate, so that the flame retardancy is V-0 level, and the thermal stress at 288°C reaches more than 50s; at the same time, the rigidity of the laminate base paper is reduced and the flexibility is improved, so that the impact strength of the bending deflection of the copper clad laminate prepared using the laminate base paper is significantly improved, the maximum bending deflection of the copper clad laminate is 3.3-3.6mm, the maximum bending load is 92-95N, and the impact strength is 83-86kJ / m 2 The deflection and load are significantly improved compared with the comparative copper clad laminate, and it has a lower water absorption rate (0.057-0.060%).
[0106] The laminated board base paper provided by the present invention is prepared from plant fibers of a specific composition, a wet strength agent of a specific composition and a flame retardant of a specific composition. The plant fibers, the composite wet strength agent and the composite flame retardant form a rich and stable chemical cross-linking network, so that the laminated board base paper has excellent adhesive impregnation, flame retardancy, heat resistance, mechanical strength, flexibility and processability.
[0107] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A halogen-free laminate base paper, characterized in that: The raw materials for preparing the halogen-free laminate base paper include plant fiber, composite wet strength agent and composite flame retardant; The plant fibers include softwood fibers, hardwood fibers, cotton fibers, and peanut shell fibers; The composite wet strength agent includes JH-1225 wet strength agent and polyethyleneimine resin; The composite flame retardant comprises cardanol-modified phenolic resin and ammonium polyphosphate flame retardant; The method for preparing the halogen-free laminate base paper comprises the following steps: S1-1. The plant fiber is mixed with a composite wet strength agent and slurried, formed on the net, to obtain base paper; S1-2. The base paper is immersed in a composite flame retardant and then dried to obtain the halogen-free laminate base paper.
2. The halogen-free laminate base paper according to claim 1, characterized in that: The plant fiber comprises the following components by weight:
3. The halogen-free laminate base paper according to claim 2, characterized in that: The fiber length of the hardwood fiber is 0.6-1.0 mm, the fiber length of the softwood fiber is 3.1-3.5 mm, the fiber length of the cotton fiber is 10-15 mm, and the fiber length of the peanut shell fiber is 0.15-0.27 mm.
4. The halogen-free laminate base paper according to claim 1, characterized in that: The composite wet strength agent comprises the following components by weight: JH-1225 wet strength agent 20 parts; 5-7 parts of polyethyleneimine resin.
5. The halogen-free laminate base paper according to claim 1, characterized in that: The composite flame retardant comprises the following components by weight: 20-30 parts of cardanol modified phenolic resin; 10 parts of ammonium polyphosphate flame retardant.
6. The halogen-free laminate base paper according to claim 5, characterized in that: The preparation method of the cardanol-modified phenolic resin comprises the following steps: S1. Cashew nut shell liquid, phenol and formaldehyde aqueous solution were put into a reactor in a mass ratio of 1:4:6 and stirred at a stirring speed of 500 r / min for 1 h, wherein the concentration of the formaldehyde aqueous solution was 30 wt%; S2. Adding aqueous hydrochloric acid to adjust the system pH = 2, heating the reactor to 60 ° C and reacting for 10 hours to obtain a polymer product, and the obtained polymer product is self-flowing to a dehydration kettle, wherein the concentration of the aqueous hydrochloric acid solution is ≥95wt%; S3. Heat the dehydration kettle to 130°C, perform high-temperature dehydration on the polymerization product for 1 hour, reduce the temperature to 90°C, turn on the vacuum pump for vacuum dehydration, and obtain cardanol-modified phenolic resin, wherein the vacuum dehydration time is 6 hours and the vacuum degree is 0.09Mpa.
7. The halogen-free laminate base paper according to claim 6, characterized in that: The cashew nut shell oil contains ≥80wt% of cardanol.
8. The halogen-free laminate base paper according to claim 1, characterized in that: When the plant fiber is mixed with the composite wet strength agent, the added amount of the composite wet strength agent is (10-13) g of the composite wet strength agent per 100 g of absolute dry weight of the plant fiber.
9. The method for preparing the halogen-free laminate base paper according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S2-1. Place coniferous wood fiber, hardwood wood fiber, cotton fiber and peanut shell fiber in a hydraulic pulper according to a ratio for mixing and crushing, and obtain crushed pulp after crushing in the hydraulic pulper for 12-20 minutes. The crushed pulp is transported to a pulp storage tank, and then beaten by a deflaker and two disc refiners in series, so that the beating degree of the crushed pulp is controlled at (20-23) ° SR, and the fiber wet weight is (1.0-1.5) g, to obtain qualified pulp; S2-2. The qualified slurry is transported to a slurry mixing tank, and the composite wet strength agent is added thereto, and then the slurry is mixed, wherein (10-13) g of the composite wet strength agent is added to every 100 g of the absolute dry amount of the qualified slurry to obtain a modulated slurry; S2-3. The pulp after pulping is sent to the pressure screen for screening after passing through the first-stage three-stage purification system of good pulp countercurrent, dilution in the white water tower and pulp flushing by the pulp flushing pump to obtain the pulp on the screen; the pulp on the screen is wet-formed in the screen part of the front box of the screen through the stabilizing box and the head box to obtain the wet paper web; the wet paper web is pressed and dried to obtain the base paper, and the moisture content of the base paper is ≤10%; S2-4. The composite flame retardant and the solvent are mixed at a material-liquid ratio of 1:5 g / mL to prepare an impregnation solution, the base paper is immersed in the impregnation solution for 50 seconds, and then extruded, pressed and dried to obtain a halogen-free laminate base paper, the halogen-free laminate base paper having a thickness of 0.270 ± 0.02 mm and a basis weight of 140 g / m 2 ; The solvent is a mixture of 65 wt % ethanol aqueous solution and 60 wt % acetone aqueous solution in a volume ratio of 1:
1.
10. Use of the halogen-free laminate base paper according to any one of claims 1 to 9 in copper-clad laminates or prepregs.
Citation Information
Patent Citations
Cashew shell modified alkyd resin and preparation method thereof
CN101143917A
Cardanol modifying phenolic resin composition and method for producing environmental protection type flame-proof paper-base copper-coating board
CN101265352A
Preparation method of cardanol modified phenolic resin
CN102363643A
Cashew nut shell oil-modified phenolic resin as well as preparation method and application thereof
CN103073690A
Production process of base paper of impregnating and flame retarding type copper foil clad plate for printed circuit board
CN106498807A
Cited By
Cationic polyurethane wet strength agent for papermaking and preparation method thereof
CN119736815A